(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing encompasses a group of technologies enabling the generation of complex, biomimetic 3D structures for tissue engineering and regenerative medicine. The ability of 3D printing to pattern multiple materials, cell types and biomolecules provides a unique tool to create tissue constructs closely resembling the composition, architecture and function of biological tissues. This keynote provides a concise overview of recent advances on the use of additive manufacturing and materials for the fabrication of cell-laden constructs and multi-functional and hierarchical scaffolds for tissue engineering.